God and war American civil religion since 1945 - Haberski, Raymond J., 1968- (New Brunswick, N.J. : Rutgers University Press, 2012)
Raymond Haberski argues that since 1945 the common moral assumptions expressed in an American civil religion have become increasingly defined by the nation's experience with war. God and War traces how three great postwar "trials"--The Cold War, the Vietnam War, and the War on Terror--have revealed the promise and terror of an American civil religion. With the tenth anniversary of 9/11 behind us and the subsequent wars in Iraq and Afghanistan winding down, Americans might now explore whether civil religion can exist apart from the power of war to affirm the value of the nation to it.
Lincoln's bequest -- Civil religion incorporated -- Civil religion redeemed -- Civil religion reborn -- Civil religion at bay -- Civil religion forsaken -- Reckoning with American civil religion.
Description based on print version record.
Keywords: Civil religion -- United States; United States -- Religion -- 1945-; United States -- History, Military -- Religious aspects; Religion; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books